(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
Samples of three healthy, diseases free, commonly consumed vegetables in Nasarawa State, Nigeria were studied for comparative nutritional evaluation with respect to proximate and amino acid compositions. The samples (Piper guineense, Spinacia oleracea and Gongronema latifolium) contained moisture in the ranged between 4.19 and 9.25%. Highest values were recorded for Spinacia oleracea and Piper guineense. Ash value was higher in S. oleracea (25.38%) comparable to G. latifolium (13.15%) and P. guineense (14.25%). The dietary fiber content ranged from 8.52% in S. oleracea to 15.18% in G. latifolium. The protein content was within the range of 18.61 to 26.12%. The amino acid analysis revealed that all the samples contained nutritionally useful quantities of most of the essential amino acids. Leucine (7.35 to 8.16 g/100 g crude protein) was the outstanding essential amino acid in this research. The total essential amino acids (with His) ranged between 38.67 g/100g cp (52.41%) in P. guineense to 40.53 g/100g cp (54.82%) in G. latifolium. The limiting AAs were Met + Cys, Thr and Met + Cys for P. guineense, S. oleracea and G. latifolium, respectively. The dietary formula based on this report showed that some essential amino acid supplementations such as Lys, Met + Cys, Thr and Val will be required in all the studied samples.